Exploring activity-induced dental modifications in medieval Pieve di Pava (central Italy, 10th-12th centuries AD). (August 2022) - Monaco, Martina; Riccomi, Giulia; Minozzi, Simona; Campana, Stefano; Giuffra, Valentina
Abstract: Objective: This study aims to investigate the following aspects: i) presence of activity-induced dental modifications (AIDMs) in a medieval population from Pieve di Pava (Siena, central Italy); ii) sex-specific and age-specific distribution of AIDMs in the sample; iii) potential correlations between AIDMs and the tradi tional activities and cultural habits of rural communities in medieval Italy. Design: The permanent teeth of 204 individuals buried at Pieve di Pava (10th-12th centuries AD) were systematically examined in order to assess the distribution of five types of AIDM, i.e. lingual surface attrition of the maxillary anterior teeth (LSAMAT), excessive occlusal load, grooving, notching, and chipping. Results: Prevalence rates of LSAMAT, excessive occlusal load and grooving were low, whereas higher frequencies were recorded for the other types of AIDMs. Prevalence was higher in the male subsample for all the modifications recorded. Overall, the frequencies of AIDMs increased with age. Conclusions: The very low prevalence of LSAMAT was thought to be connected to leatherworking in the sample under study, while excessive occlusal load was interpreted as evidence that hard materials requiring preliminary chewing and softening were not regularly processed with teeth. The unique case of interproximal grooving in an old male individual may reflect the use of a toothpick for therapeutic purpose. Conversely, the very high prevalence of notching and chipping was taken as indicative of the processing of wool fibers. The sex-specific distribution of these AIDMs suggests that males performed activities involving the use of teeth more frequently than females. Highlights: One of the few studies focussed on extramasticatory dental wear in medieval Italy. Males displayed higher prevalence rates of dental defects compared to females. Two cases of interproximal grooving were identified in an old adult male. Prevalence rates of notching and chipping were probably linked to fiber processing.